2008
DOI: 10.1136/jech.2008.078741
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic disparity in stillbirth and infant mortality in Denmark 1981-2003

Abstract: Among the five largest ethnic minorities, the Turkish. Pakistani and Somali population had substantially higher fetal and infant mortality compared with the Danish majority population, while the Lebanese and Former Yugoslavian minorities were at the same level as the majority population. The excess risk was not attributable to socioeconomic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 34 publications
8
57
1
Order By: Relevance
“…Nonetheless, in Norway data on familial relationships are systematically registered for all births, and results from a large registry study 17 on consanguinity and birth defects showed that 28% of birth defects could be attributed to consanguinity in Pakistani offspring. Registration in Norway has showed that 40% of second generation Pakistani, 17% of second generation Turkish and 7% of second generation Somali children have consanguine parents 3 , but the proportion has been decreasing over time. 19 It is likely that a similar pattern could be present in Denmark.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, in Norway data on familial relationships are systematically registered for all births, and results from a large registry study 17 on consanguinity and birth defects showed that 28% of birth defects could be attributed to consanguinity in Pakistani offspring. Registration in Norway has showed that 40% of second generation Pakistani, 17% of second generation Turkish and 7% of second generation Somali children have consanguine parents 3 , but the proportion has been decreasing over time. 19 It is likely that a similar pattern could be present in Denmark.…”
Section: Discussionmentioning
confidence: 99%
“…3 Results showed an increased stillbirth and infant mortality rate among ethnic Turkish, Pakistani and Somali children compared with ethnic Danish children, with a doubled risk of death before the child reached their one-year birthday. These results are in concordance with evidence from previous international studies 4-13 , where an increased risk of death in infancy was seen for offspring of immigrants.…”
Section: Introductionmentioning
confidence: 97%
“…Our results are supported by those of other studies conducted in Scandinavia, which indicated that infant mortality varies depending on the maternal source country. For example, Villadsen, Mortensen, and Andersen (2009) found that the Pakistani, Somali, and Turkish populations had substantially higher infant mortality rates than the Danish population. While Vangen et al (2002), using a Norwegian dataset, found significantly higher mortality rates among infants whose mothers were from Pakistan, they found no significant effects for infants whose mothers were from Vietnam and North Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Population-covering records in the period 1981-2003 informed of higher relative risk of stillbirth for 3 of the 5 largest ethnic minorities residing in Denmark (Villadsen et al 2009). This higher risk could not be attributed to unfavourable socioeconomic conditions.…”
Section: Discussionmentioning
confidence: 99%